Iatrogenic Fistula in Hemodialysis Patients: An Alternative Approach to Thrombectomy of Arteriovenous Graft (AVG) Thrombosis. (16th April 2022) - Dukkipati, Ramanath; Benjo, Alexandre M.; Jimenez, Antonio; Lukitsch, Ivo; Echefu, Gift C.; Kumbala, Damodar R.
Abstract : Arterial venous (AV) fistula is the first choice of vascular access to perform hemodialysis in the vast majority of suitable patients followed by arteriovenous grafts (AVG). An iatrogenic fistula can occur when a second vein adjacent to the graft is punctured and the needle traverses the vein. In normal circumstances, this has no clinical repercussions and does not need correction, and in prior reports, it has helped to maintain the patency of partially occluded grafts but rarely can lead to thrombosis of the graft due to reduced flow and pressure in the graft lumen. We report here what we believe is a unique approach to perform thrombectomy of an occluded graft in a 71-year-old patient on hemodialysis to avoid placement of tunneled hemodialysis catheters and complications associated with catheters. When the outflow of basilic vein in this patient was thrombosed and could not be traversed, we successfully used an iatrogenic fistula as main outflow vein for the graft and created an alternative vein for drainage thus avoiding placement of a tunneled catheter for hemodialysis.